Pengaruh Kesadaran Pajak, Sosialisasi Perpajakan, Sanksi Perpajakan, Layanan E-Commerce Terhadap Kepatuhan Wajib Pajak Kendaraan - Yahya, Dion Yuzhar; Murdiawati, Dewi; Prananjaya, Kadek Pranetha (Lentera Barasaki Publishing House, 2024)
Indonesia as a developing country will continue to improve the quality of national development to improve people's living standards. To carry out national development, of course, requires quite a large amount of funding, one source of funding obtained by the government is from tax collection. The aim of this research is to analyze the relationship between the influence of tax awareness, tax socialization, tax sanctions and e-commerce services. The research data used uses primary data. Data was obtained from a questionnaire distributed to registered motor vehicle taxpayers in Sidoarjo Regency. The number of questionnaires distributed was 160 questionnaires, of which only 126 questionnaires could be processed. Data were processed using multiple linear regression analysis tests using the SPPS. The result inform that the tax awareness variable has a partial effect on vehicle tax compliance and the tax socialization variable has no partial effect on vehicle tax compliance. The findings also inform that the tax sanctions variable has a partial effect on vehicle tax compliance and the e-commerce service variable has a partial effect on vehicle tax compliance.